Optimum Design of Multidischarge Outlet Biomass Briquetting Machine - Jiaqi Yang; Jirong Wang; Jun Li; Lianwen Shi; Xiangwu Dai (Complexity)
A high-efficiency biomass material was designed according to the densification mechanism of biomass. This machine improved the efficiency by recombining the feeding stage, prepressing stage, compaction stage, pressure-holding stage, and pushing stage of the compression process, so that part of the working stages was carried out simultaneously. To further improve efficiency and rationally allocate power at each stage, in this paper, we established a mathematical model for the machine. We use the nonlinear programming in Matlab (2016b) to solve the minimum value of the model, making the machine work time the shortest.